Peningkatan Kemampuan Pemecahan Masalah Melalui Pendekatan Kontekstual - Khairani, Siti; Surya, Edi; Fauzi, Kms. Muhammad Amin (Cybernetics: Journal Educational Research and Social Studies, 2024)
The aim of this research is to find out: 1) increasing students' problem solving abilities through a contextual approach. The subjects in this research were 30 class V students at SDN 00312 Pargarutan Jae and the object of this research was to see improvements in the learning process carried out by looking at students' mathematical problem solving abilities. Based on the findings presented in the previous section, several conclusions can be drawn relating to learning factors, mathematical problem solving abilities. These conclusions are that the increase in mathematical problem solving abilities of students who are given contextual learning is higher than students who are given regular learning.